STRATEGI PELESTARIAN BUDAYA OJHUNG MADURA DI ERA GLOBAL - Taufiqur Rahman; Faisol Gunawan; Dian Altika Sari; Mohammad Herli (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2019)
Ojhung culture is one of the local culture in Madura. Existence is motivated by people's desire for rain on drought in some parts of Madura. The Existence of “Ojhung” madura is currently imposing, where the attention of the younger generation and the government was minimal. It is feared will lead to the sinking of this culture in Madura. This research was conducted with the aim to formulate the right strategy for cultural preservation efforts Ojhung Madura, it is expected this will be a recommendation for the parties concerned for the preservation of the culture. To answer the problems that occur, we used qualitative method with phenomenological approach. The use of this method is carried out to reveal the cultural phenomenon Ojhung and preservation strategies. The strategy formulation process we involve stakeholders as informants such as Actors Ojhung match, chairman Ojhung community, local government, as well as cultural Madura. The results of the study resulted in recommendations for the strategy of cultural preservation efforts Ojhung Madura. The formulation of the strategy through a SWOT analysis shows that cultural preservation Ojhung Madura require their attention from the local government, the younger generation, as well as the local community. Improvements to the management (match) Ojhung culture also required include increased promotion, event format, as well as efforts to Ojhung performances scheduled on the agenda of local travel (Sumenep).